Peripheral Blood-Derived Stem Cells for the Treatment of Cartilage Injuries: A Systematic Review - Zhu, Yanlin; Fu, Weili (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: Background: The treatment of cartilage damage is a hot topic at present, and cell therapy is an emerging alternative therapy. Stem cells derived from peripheral blood have become the focus of current research due to the ease of obtaining materials and a wide range of sources. Method: We used a text search strategy using the ("mesenchymal stem cells " [MeSH term] OR "MSC" OR "BMMSC" OR “PBMSC” OR” PBMNC” OR “peripheral blood stem cells”) AND (cartilage injury [MeSH term] OR "cartilage" OR “chondral lesion”). After searching the literature, through the inclusion and exclusion criteria, the last included articles were systematically reviewed Result: we found that peripheral blood-derived stem cells have chondrogenic differentiation ability and can induce chondrogenic differentiation and repair in vivo, and have statistical significance in clinical and imaging prognosis. improvement of academic differences. Compared with bone marrow, peripheral blood is easier to obtain, widely sourced and simple to obtain. In the future, peripheral blood is a more potential cell source for cell therapy in the treatment of cartilage damage. Conclusion: Stem cells derived from peripheral blood have the ability to repair cartilage and are an important resource for the treatment of cartilage damage in the future. The specific mechanism and way of its repairing cartilage need further study.